Pengaruh Trust, Commitment, Brand Image, Service Quality, dan Customer Value terhadap Customer Satisfaction: Studi Kasus pada Nasabah BSI di Jakarta - Putri, Tasya Mega; Briliana, Vita (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to analyze and determine the impact of trust, commitment, brand image, service quality, and customer value towards customer satisfaction of Bank Syariah Indonesia (BSI). The research design that has been used for this study are descriptive and causality research, using a Likert Scale with five points measurement. The sample selection in this study used a purposive sampling method with primary and secondary data, and the number of respondents was 120 respondents. The data analysis method used in this study is multiple linear regression. The results of this study has shown that service quality and customer value have an effect on customer satisfaction at Bank Syariah Indonesia (BSI), however, trust, commitment, and brand image have no effect on customer satisfaction at Bank Syariah Indonesia (BSI).